Il contributo dell’Università degli Studi di Milano negli scavi di Gortina: il materiale ceramico proveniente dalle Terme a Sud del Pretorio (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2010)
This text proposes an analysis of the problems relevant to the main productions of Gortinian local pottery (certificate, production and circulation in the Cretan center sites)  starting from the pottery of the excavation in the Thermae to the south of Pretorio discovered during the 2003-2009 missions by the Milan University (Director: Prof. G. Bejor).  Starting the research from a first classification of the available documents, the basis for the analysis of some problems relevant to production, use and circulation of the pottery and to the relationship between handmade pottery and daily life are created. The above with a particular care for the production of fine pottery and, particularly, of the local over-painted Byzantine and Demetrian ware.